Penguatan Kosakata Bahasa Inggris Mahasiswa Baru melalui Pembelajaran Kontekstual Berbasis Teks Prosedur dalam Kegiatan Pengolahan Limbah - Puspitasari, Ema; Hamatun; Rusmalinda, Riski; Umam, Lukman Habibul; Mustofa, Yusuf; Khoiri, Khabibul (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2025)
The management of household waste into granular fertilizer has great potential to support sustainable agriculture while enhancing community environmental literacy. This community service program was conducted in Giriklopomulyo Village, Sekampung District, East Lampung, through a participatory training approach and hands-on practice involving community leaders and two invited experts. Students were also engaged in the waste processing sessions and the preparation of procedural texts based on field experiences. The evaluation results indicated significant improvements in participants’ knowledge, technical skills, ecological awareness, and functional literacy. In addition, participants’ vocabulary mastery related to environmental and agricultural terms increased by 35% as shown in the pre-test and post-test results. The hands-on method proved effective in encouraging active involvement of both the community and students in addressing waste management issues. This program demonstrates that collaboration between universities and rural communities can create locally based, applicable solutions. These findings are essential as a foundation for developing similar programs in other regions with high organic waste potential.